BARRIERS TO PUBLIC-PRIVATE PARTNERSHIPS IN THE CONSTRUCTION SECTOR IN IRAQ - Ruaa Mahdi; Özge Alboğa; Ahmad Reshad Noorı; Serkan Aydınlı (Konya Journal of Engineering Sciences, 2026)
During the management of public-private partnerships (PPPs), numerous barriers may arise that could negatively affect the implementation of partnerships in investment projects. For developing economies such as Iraq, where the PPP project delivery system has a high potential to offer significant benefits, it is important to identify the barriers to the system in a hierarchical manner. This study aims to identify the barriers that prevent the adoption of PPPs in Iraq's construction sector. First, potential barriers were identified through a literature review. Subsequently, a survey focusing on four main categories of barriers (legal, technical, implementation, and political) was administered to sector professionals in Iraq. The analytic hierarchy process method was used to determine the importance of the barrier groups. The findings indicate that legal barriers were found to have the highest impact on the PPPs in Iraq, technical barriers and implementation barriers have equally impact, and political barriers were found to be the least influential barrier group. Additionally, it was determined that most of the barriers contributing to the failure of PPPs projects stem from misguidance by consultants in decision-making processes. The study suggests that identifying potential challenges related to public-private partnership legislation could be beneficial in helping Iraq become a country with a high standard of living at all levels.